Kualitas Pelayanan Kartu Tanda Penduduk Elektronik Di Dinas Kependudukan dan Pencatatan Sipil Kota Palu - Burhanuddin Soenoe; Selfana Selfana; M. Nur Alamsyah (Jurnal ADMINISTRATOR, 2021)
This study examines the Quality of Electronic Identity Card Services at the Department of Population and Civil Registration of Palu City. The types of data used are primary data and secondary data. Data collection techniques, carried out through observation, interviews, and documentation. Informant withdrawal technique using purposive. The number of informants in this study amounted to 5 people. The theory used is the theory of Zethmal, Parasuraman and Berry, which consists of 5 (five) aspects : tangibles, reliability, responsiveness, assurance and empathy. Based on the results of research conducted, that the quality of Electronic Identity Card Services at the Population and Civil Registration Office of Palu City is not optimal. First; tangibles, namely inadequate facilities and infrastructure such as the lack of space for waiting rooms and limited available seats, as well as public toilets that look unclean. But in terms of the appearance of the apparatus is quite good. Second; reliability, namely the ability of the apparatus to use assistive devices is good, it's just that the services provided do not fully refer to the service flow. Third; responsiveness, namely the response of the apparatus who received the applicant's complaint was very good, but the speed of processing electronic identity cards was not maximized. Fourth; assurance, which is the guarantee given by the apparatus to the applicants that is not on time. However, the permit fee charged is in accordance with applicable regulations. Fifth; empathy, namely the service provided is not discriminatory and the apparatus always provides courteous and friendly service. Thus, from the five aspects of service quality above, there are still several things that need to be addressed, so that the quality of service provided can be maximized